Virulence in Mice of a Toxoplasma gondii Type II Isolate Does Not Correlate With the Outcome of Experimental Infection in Pregnant Sheep - Sánchez-Sánchez, Roberto; Ferre, Ignacio; Regidor-Cerrillo, Javier; Gutiérrez-Expósito, Daniel; Ferrer, Luis Miguel; Arteche-Villasol, Noive; Moreno-Gonzalo, Javier; Müller, Joachim; Aguado-Martínez, Adriana; Pérez, Valentín; Hemphill, Andrew; Ortega-Mora, Luis Miguel; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is an apicomplexan parasite that infects almost all warm-blooded animals. Little is known about how the parasite virulence in mice extrapolates to other relevant hosts. In the current study, in vitro phenotype and in vivo behavior in mice and sheep of a type II T. gondii isolate (TgShSp1) were compared with the reference type II T. gondii isolate (TgME49). The results of in vitro assays and the intraperitoneal inoculation of tachyzoites in mice indicated an enhanced virulence for the laboratory isolate, TgME49, compared to the recently obtained TgShSp1 isolate. TgShSp1 proliferated at a slower rate and had delayed lysis plaque formation compared to TgME49, but it formed more cyst-like structures in vitro. No mortality was observed in adult mice after infection with 1–105 tachyzoites intraperitoneally or with 25–2,000 oocysts orally of TgShSp1. In sheep orally challenged with oocysts, TgME49 infection resulted in sporadically higher rectal temperatures and higher parasite load in cotyledons from ewes that gave birth and brain tissues of the respective lambs, but no differences between these two isolates were found on fetal/lamb mortality or lesions and number of T. gondii-positive lambs. The congenital infection after challenge at mid-pregnancy with TgShSp1, measured as offspring mortality and vertical transmission, was different depending on the challenged host. In mice, mortality in 50% of the pups was observed when a dam was challenged with a high oocyst dose (500 TgShSp1 oocysts), whereas in sheep infected with the same dose of oocysts, mortality occurred in all fetuses. Likewise, mortality of 9 and 27% of the pups was observed in mice after infection with 100 and 25 TgShSp1 oocysts, respectively, while in sheep, infection with 50 and 10 TgShSp1 oocysts triggered mortality in 68 and 66% of the fetuses/lambs. Differences in vertical transmission in the surviving offspring were only found with the lower oocyst doses (100% after infection with 10 TgShSp1 oocysts in sheep and only 37% in mice after infection with 25 TgShSp1 oocysts). In conclusion, virulence in mice of T. gondii type II isolates may not be a good indicator to predict the outcome of infection in pregnant sheep.